Investigation of growth dynamics of carbon nanotubes - Kharlamova, Marianna V. (Beilstein Journal of Nanotechnology, 2017)
The synthesis of single-walled carbon nanotubes (SWCNTs) with defined properties is required for both fundamental investigations and practical applications. The revealing and thorough understanding of the growth mechanism of SWCNTs is the key to the synthesis of nanotubes with required properties. This paper reviews the current status of the research on the investigation of growth dynamics of carbon nanotubes. The review starts with the consideration of the peculiarities of the growth mechanism of carbon nanotubes. The physical and chemical states of the catalyst during the nanotube growth are discussed. The chirality selective growth of nanotubes is described. The main part of the review is dedicated to the analysis and systematization of the reported results on the investigation of growth dynamics of nanotubes. The studies on the revealing of the dependence of the growth rate of nanotubes on the synthesis parameters are reviewed. The correlation between the lifetime of catalyst and growth rate of nanotubes is discussed. The reports on the calculation of the activation energy of the nanotube growth are summarized. Finally, the growth properties of inner tubes inside SWCNTs are considered.
Keywords: activation energy; carbon nanotube; growth dynamics; growth rate; synthesis

(untitled) - Bethune, D. S.; Kiang, C. H.; de Vries, M. S.; Gorman, G.; Savoy, R.; Vazquez, J.; Beyers, R. (Nature, 1993)

(untitled) - Iijima, S.; Ichihashi, T. (Nature, 1993)

Physical properties of сarbon nanotube - Saito, R.; Dresselhaus, G.; Dresselhaus, M. S. (Imperial College Press, 1998)

(untitled) - Charlier, J.-C.; Blase, X.; Roche, S. (Rev. Mod. Phys., 2007)

Carbon Nanotubes: Topics in Applied Physics - Dai, H. J. (Nanotube growth and characterization, 2001)

Carbon Nanotubes: Topics in Applied Physics - Joselevich, E.; Dai, H. J.; Liu, J.; Hata, K.; Windle, A. H. (Carbon nanotube synthesis and organization, 2008)

(untitled) - Ding, L.; Tselev, A.; Wang, J. Y.; Yuan, D. N.; Chu, H. B.; McNicholas, T. P.; Li, Y.; Liu, J. (Nano Lett., 2009)

(untitled) - Li, Y. M.; Mann, D.; Rolandi, M.; Kim, W.; Ural, A.; Hung, S.; Javey, A.; Cao, J.; Wang, D. W.; Yenilmez, E.; Wang, Q.; Gibbons, J. F.; et al. (Nano Lett., 2004)

(untitled) - Avouris, P.; Chen, Z. H.; Perebeinos, V. (Nat. Nanotechnol., 2007)

(untitled) - Bachtold, A.; Hadley, P.; Nakanishi, T.; Dekker, C. (Science, 2001)

(untitled) - Chen, Z. H.; Appenzeller, J.; Lin, Y. M.; Sippel-Oakley, J.; Rinzler, A. G.; Tang, J. Y.; Wind, S. J.; Solomon, P. M.; Avouris, P. (Science, 2006)

(untitled) - Tans, S. J.; Verschueren, A. R. M.; Dekker, C. (Nature, 1998)

(untitled) - Artukovic, E.; Kaempgen, M.; Hecht, D. S.; Roth, S.; Grüner, G. (Nano Lett., 2005)

(untitled) - Cao, Q.; Kim, H.-S.; Pimparkar, N.; Kulkarni, J. P.; Wang, C. J.; Shim, M.; Roy, K.; Alam, M. A.; Rogers, J. A. (Nature, 2008)

(untitled) - Huang, Y. X.; Palkar, P. V.; Li, L.-J.; Zhang, H.; Chen, P. (Biosens. Bioelectron., 2010)

Handbook of Carbon Nano Materials - Kharlamova, M. V. (Single-walled Carbon Nanotubes: Synthesis and Modification of the Electronic Structure, 2015)

(untitled) - Yan, Y. B.; Miao, J. W.; Yang, Z. H.; Xiao, F.-X.; Yang, H. B.; Liu, B.; Yang, Y. H. (Chem. Soc. Rev., 2015)

(untitled) - Kharlamova, M. V. (Prog. Mater. Sci., 2016)

(untitled) - Baker, R. T. K.; Barber, M. A.; Harris, P. S.; Feates, F. S.; Waite, R. J. (J. Catal., 1972)

(untitled) - Baker, R. T. K.; Harris, P. S.; Thomas, R. B.; Waite, R. J. (J. Catal., 1973)

Chemistry and Physics of Carbon - Baker, R. T. K.; Harris, P. S. (The formation of filamentous carbon, 1978)

(untitled) - Wagner, R. S.; Ellis, W. C. (Appl. Phys. Lett., 1964)

(untitled) - Jourdain, V.; Bichara, C. (Carbon, 2013)

(untitled) - Benissad, F.; Gadelle, P.; Coulon, M.; Bonnetain, L. (Carbon, 1988)

(untitled) - Tibbetts, G. G.; Bernardo, C. A.; Gorkiewicz, D. W.; Alig, R. L. (Carbon, 1994)

(untitled) - Madroñero, A. (J. Mater. Sci., 1995)

(untitled) - Kukovitsky, E. F.; L'vov, S. G.; Sainov, N. A. (Chem. Phys. Lett., 2000)

(untitled) - Kanzow, H.; Ding, A. (Phys. Rev. B, 1999)

(untitled) - Gavillet, J.; Loiseau, A.; Journet, C.; Willaime, F.; Ducastelle, F.; Charlier, J.-C. (Phys. Rev. Lett., 2001)

(untitled) - Ding, F.; Rosén, A.; Bolton, K. (Chem. Phys. Lett., 2004)

(untitled) - Ding, F.; Bolton, K.; Rosén, A. (J. Phys. Chem. B, 2004)

(untitled) - Ding, F.; Bolton, K.; Rosén, A. (Comput. Mater. Sci., 2006)

(untitled) - Tessonnier, J.-P.; Su, D. S. (ChemSusChem, 2011)

Carbon Nanotubes - Synthesis, Characterization, Applications - Kumar, M. (Carbon Nanotube Synthesis and Growth Mechanism, 2011)

(untitled) - Baird, T.; Fryer, J. R.; Grant, B. (Nature, 1971)

(untitled) - Evans, E. L.; Thomas, J. M.; Thrower, P. A.; Walker, P. L. (Carbon, 1973)

(untitled) - Rostrup-Nielsen, J.; Trimm, D. L. (J. Catal., 1977)

(untitled) - Klinke, C.; Bonard, J.-M.; Kern, K. (Phys. Rev. B, 2005)

(untitled) - Oberlin, A.; Endo, M.; Koyama, T. (J. Cryst. Growth, 1976)

(untitled) - Yang, R. T.; Chen, J. P. (J. Catal., 1989)

(untitled) - Helveg, S.; López-Cartes, C.; Sehested, J.; Hansen, P. L.; Clausen, B. S.; Rostrup-Nielsen, J. R.; Abild-Pedersen, F.; Nørskov, J. K. (Nature, 2004)

(untitled) - Hofmann, S.; Csányi, G.; Ferrari, A. C.; Payne, M. C.; Robertson, J. (Phys. Rev. Lett., 2005)

(untitled) - Seidel, R.; Duesberg, G. S.; Unger, E.; Graham, A. P.; Liebau, M.; Kreupl, F. (J. Phys. Chem. B, 2004)

(untitled) - Raty, J.-Y.; Gygi, F.; Galli, G. (Phys. Rev. Lett., 2005)

(untitled) - Nessim, G. D. (Nanoscale, 2010)

(untitled) - Chen, Y. B.; Zhang, J. (Carbon, 2011)

(untitled) - Takagi, D.; Kobayashi, Y.; Hommam, Y. (J. Am. Chem. Soc., 2009)

(untitled) - Steiner, S. A., III; Baumann, T. F.; Bayer, B. C.; Blume, R.; Worsley, M. A.; MoberlyChan, W. J.; Shaw, E. L.; Schlögl, R.; Hart, A. J.; Hofmann, S.; Wardle, B. L. (J. Am. Chem. Soc., 2009)

(untitled) - Liu, B. L.; Tang, D.-M.; Sun, C. H.; Liu, C.; Ren, W. C.; Li, F.; Yu, W.-J.; Yin, L.-C.; Zhang, L. L.; Jiang, C. B.; Cheng, H.-M. (J. Am. Chem. Soc., 2011)

(untitled) - Moisala, A.; Nasibulin, A. G.; Kauppinen, E. I. (J. Phys.: Condens. Matter, 2003)

Smoke, Dust, and Haze - Friedlander, S. K. (Oxford University Press, 2000)

(untitled) - Wirth, C. T.; Hofmann, S.; Robertson, J. (Diamond Relat. Mater., 2009)

(untitled) - Ding, F.; Bolton, K.; Rosén, A. (J. Vac. Sci. Technol., A, 2004)

(untitled) - Qi, Y.; Çağin, T.; Johnson, W. L.; Goddard, W. A., III (J. Chem. Phys., 2001)

(untitled) - Diarra, M.; Zappelli, A.; Amara, H.; Ducastelle, F.; Bichara, C. (Phys. Rev. Lett., 2012)

(untitled) - Harutyunyan, A. R.; Tokune, T.; Mora, E. (Appl. Phys. Lett., 2005)

(untitled) - Ago, H.; Ohshima, S.; Uchida, K.; Yumura, M. (J. Phys. Chem. B, 2001)

(untitled) - Saito, T.; Ohshima, S.; Xu, W.-C.; Ago, H.; Yumura, M.; Iijima, S. (J. Phys. Chem. B, 2005)

(untitled) - Hofmann, S.; Sharma, R.; Ducati, C.; Du, G.; Mattevi, C.; Cepek, C.; Cantoro, M.; Pisana, S.; Parvez, A.; Cervantes-Sodi, F.; Ferrari, A. C.; Dunin-Borkowski, R.; et al. (Nano Lett., 2007)

(untitled) - Lin, M.; Tan, J. P. Y.; Boothroyd, C.; Loh, K. P.; Tok, E. S.; Foo, Y.-L. (Nano Lett., 2007)

(untitled) - Yoshida, H.; Takeda, S.; Uchiyama, T.; Kohno, H.; Homma, Y. (Nano Lett., 2008)

(untitled) - Yoshida, H.; Shimizu, T.; Uchiyama, T.; Kohno, H.; Homma, Y.; Takeda, S. (Nano Lett., 2009)

(untitled) - Hofmann, S.; Blume, R.; Wirth, C. T.; Cantoro, M.; Sharma, R.; Ducati, C.; Hävecker, M.; Zafeiratos, S.; Schnoerch, P.; Oestereich, A.; Teschner, D.; Albrecht, M.; et al. (J. Phys. Chem. C, 2009)

(untitled) - Lin, M.; Tan, J. P. Y.; Boothroyd, C.; Loh, K. P.; Tok, E. S.; Foo, Y.-L. (Nano Lett., 2006)

(untitled) - Esconjauregui, S.; Whelan, C. M.; Maex, K. (Carbon, 2009)

(untitled) - Emmenegger, C.; Bonard, J.-M.; Mauron, P.; Sudan, P.; Lepora, A.; Grobety, B.; Züttel, A.; Schlapbach, L. (Carbon, 2003)

(untitled) - Nishimura, K.; Okazaki, N.; Pan, L. J.; Nakayama, Y. (Jpn. J. Appl. Phys., 2004)

(untitled) - Mattevi, C.; Hofmann, S.; Cantoro, M.; Ferrari, A. C.; Robertson, J.; Castellarin-Cudia, C.; Dolafi, S.; Goldoni, A.; Cepek, C. (Physica E, 2008)

(untitled) - Ni, L.; Kuroda, K.; Zhou, L.-P.; Ohta, K.; Matsuishi, K.; Nakamura, J. (Carbon, 2009)

(untitled) - Buyanov, R. A.; Chesnokov, V. V.; Afanasev, A. D.; Babenko, V. S. (Kinet. Catal., 1977)

(untitled) - Buyanov, R. A.; Chesnokov, V. V.; Afanasev, A. D. (Kinet. Catal., 1979)

(untitled) - Chesnokov, V. V.; Buyanov, R. A.; Afanasev, A. D. (Kinet. Catal., 1979)

(untitled) - Chesnokov, V. V.; Buyanov, R. A.; Afanasev, A. D. (Kinet. Catal., 1983)

(untitled) - Chesnokov, V. V.; Buyanov, R. A. (Kinet. Catal., 1987)

(untitled) - Chesnokov, V. V.; Buyanov, R. A. (Usp. Khim., 2000)

(untitled) - de Bokx, P. K.; Kock, A. J. H. M.; Boellaard, E.; Klop, W.; Geus, J. W. (J. Catal., 1985)

(untitled) - Kock, A. J. H. M.; de Bokx, P. K.; Boellaard, E.; Klop, W.; Geus, J. W. (J. Catal., 1985)

(untitled) - Manning, M. P.; Garmirian, J. E.; Reid, R. C. (Ind. Eng. Chem. Process Des. Dev., 1982)

(untitled) - Alstrup, I. (J. Catal., 1988)

(untitled) - Schouten, F. C.; Kaleveld, E. W.; Bootsma, G. A. (Surf. Sci., 1977)

(untitled) - Schaper, A. K.; Hou, H. Q.; Greiner, A.; Phillipp, F. (J. Catal., 2004)

(untitled) - Pérez-Cabero, M.; Romeo, E.; Royo, C.; Monzón, A.; Guerrero-Ruíz, A.; Rodríguez-Ramos, I. (J. Catal., 2004)

(untitled) - Pérez-Cabero, M.; Rodríguez-Ramos, I.; Guerrero-Ruíz, A. (J. Catal., 2003)

(untitled) - Latorre, N.; Romeo, E.; Cazaña, F.; Ubieto, T.; Royo, C.; Villacampa, J. J.; Monzón, A. (J. Phys. Chem. C, 2010)

(untitled) - Zaikovskii, V. I.; Chesnokov, V. V.; Buyanov, R. A. (Kinet. Catal., 2001)

(untitled) - Chesnokov, V. V.; Buyanov, R. A.; Afanasiev, A. D. (Izv. Sib. Otd. Akad. Nauk SSSR, Ser. Khim. Nauk, 1982)

(untitled) - Chesnokov, V. V.; Zaikovskii, V. I.; Buyanov, R. A.; Molchanov, V. V.; Plyasova, L. M. (Kinet. Catal., 1994)

(untitled) - De Jong, K. P.; Geus, J. W. (Catal. Rev.: Sci. Eng., 2000)

(untitled) - Sharma, R.; Moore, E.; Rez, P.; Treacy, M. M. J. (Nano Lett., 2009)

(untitled) - Wirth, C. T.; Bayer, B. C.; Gamalski, A. D.; Esconjauregui, S.; Weatherup, R. S.; Ducati, C.; Baehtz, C.; Robertson, J.; Hofmann, S. (Chem. Mater., 2012)

(untitled) - Picher, M.; Lin, P. A.; Gomez-Ballesteros, J. L.; Balbuena, P. B.; Sharma, R. (Nano Lett., 2014)

(untitled) - Landois, P.; Rouziére, S.; Pinault, M.; Porterat, D.; Mocuta, C.; Elkaim, E.; Mayne-L'Hermite, M.; Launois, P. (Phys. Status Solidi B, 2011)

(untitled) - Wang, Z. H.; Zhang, Z. D.; Choi, C. J.; Kim, B. K. (J. Alloys Compd., 2003)

(untitled) - Zhang, J. Q.; Ostrovski, O. (ISIJ Int., 2001)

(untitled) - Wang, Y. Y.; Li, B.; Ho, P. S.; Yao, Z.; Shi, L. (Appl. Phys. Lett., 2006)

(untitled) - Li, J.; Papadopoulos, C.; Xu, J. M.; Moskovits, M. (Appl. Phys. Lett., 1999)

(untitled) - Bower, C.; Zhou, O.; Zhu, W.; Werder, D. J.; Jin, S. H. (Appl. Phys. Lett., 2000)

(untitled) - Li, Y. M.; Kim, W.; Zhang, Y. G.; Rolandi, M.; Wang, D. W.; Dai, H. J. (J. Phys. Chem. B, 2001)

(untitled) - Sharma, R.; Rez, P.; Treacy, M. M. J.; Stuart, S. J. (J. Electron Microsc., 2005)

(untitled) - He, M. S.; Jiang, H.; Kauppi, I.; Fedotov, P. V.; Chernov, A. I.; Obraztsova, E. D.; Cavalca, F.; Wagner, J. B.; Hansen, T. W.; Sainio, J.; Sairanen, E.; Lehtonen, J.; et al. (J. Mater. Chem. A, 2014)

(untitled) - Huang, S. M.; Woodson, M.; Smalley, R.; Liu, J. (Nano Lett., 2004)

(untitled) - Fiawoo, M.-F. C.; Bonnot, A.-M.; Amara, H.; Bichara, C.; Thibault-Pénisson, J.; Loiseau, A. (Phys. Rev. Lett., 2012)

(untitled) - He, M.; Magnin, Y.; Amara, H.; Jiang, H.; Cui, H.; Fossard, F.; Castan, A.; Kauppinen, E.; Loiseau, A.; Bichara, C. (Carbon, 2017)

(untitled) - Zhang, F.; Hou, P.-X.; Liu, C.; Wang, B.-W.; Jiang, H.; Chen, M.-L.; Sun, D.-M.; Li, J.-C.; Cong, H.-T.; Kauppinen, E. I.; Cheng, H.-M. (Nat. Commun., 2016)

(untitled) - Bachilo, S. M.; Balzano, L.; Herrera, J. E.; Pompeo, F.; Resasco, D. E.; Weisman, R. B. (J. Am. Chem. Soc., 2003)

(untitled) - Lolli, G.; Zhang, L. A.; Balzano, L.; Sakulchaicharoen, N.; Tan, Y. Q.; Resasco, D. E. (J. Phys. Chem. B, 2006)

(untitled) - Wang, B.; Poa, C. H. P.; Wei, L.; Li, L.-J.; Yang, Y. H.; Chen, Y. (J. Am. Chem. Soc., 2007)

(untitled) - Wang, B.; Wei, L.; Yao, L.; Li, L.-J.; Yang, Y. H.; Chen, Y. (J. Phys. Chem. C, 2007)

(untitled) - Miyauchi, Y. H.; Chiashi, S. H.; Murakami, Y.; Hayashida, Y.; Maruyama, S. (Chem. Phys. Lett., 2004)

(untitled) - Li, X. L.; Tu, X. M.; Zaric, S.; Welsher, K.; Seo, W. S.; Zhao, W.; Dai, H. J. (J. Am. Chem. Soc., 2007)

(untitled) - Chiang, W.-H.; Sankaran, R. M. (Nat. Mater., 2009)

(untitled) - Li, N.; Wang, X. M.; Ren, F.; Haller, G. L.; Pfefferle, L. D. (J. Phys. Chem. C, 2009)

(untitled) - Wang, H.; Wang, B.; Quek, X.-Y.; Wei, L.; Zhao, J. W.; Li, L.-J.; Chan-Park, M. B.; Yang, Y. H.; Chen, Y. A. (J. Am. Chem. Soc., 2010)

(untitled) - He, M. S. A.; Chernov, A. I.; Fedotov, P. V.; Obraztsova, E. D.; Rikkinen, E.; Zhu, Z.; Sainio, J.; Jiang, H.; Nasibulin, A. G.; Kauppinen, E. I.; Niemelä, M.; Krause, A. O. I. (Chem. Commun., 2011)

(untitled) - He, M.; Chernov, A. I.; Fedotov, P. V.; Obraztsova, E. D.; Sainio, J.; Rikkinen, E.; Jiang, H.; Zhu, Z.; Tian, Y.; Kauppinen, E. I.; Niemelä, M.; Krauset, A. O. I. (J. Am. Chem. Soc., 2010)

(untitled) - Ghorannevis, Z.; Kato, T.; Kaneko, T.; Hatakeyama, R. (J. Am. Chem. Soc., 2010)

(untitled) - Loebick, C. Z.; Podila, R.; Reppert, J.; Chudow, J.; Ren, F.; Haller, G. L.; Rao, A. M.; Pfefferle, L. D. (J. Am. Chem. Soc., 2010)

(untitled) - He, M. S. A.; Chernov, A. I.; Obraztsova, E. D.; Sainio, J.; Rikkinen, E.; Jiang, H.; Zhu, Z.; Kaskela, A.; Nasibulin, A. G.; Kauppinen, E. I.; Niemelä, M.; Krause, O. (Nano Res., 2011)

(untitled) - Zhu, Z.; Jiang, H.; Susi, T.; Nasibulin, A. G.; Kauppinen, E. I. (J. Am. Chem. Soc., 2011)

(untitled) - Zhao, Q. C.; Xu, Z. W.; Hu, Y.; Ding, F.; Zhang, J. (Sci. Adv., 2016)

(untitled) - Liu, B. L.; Ren, W. C.; Li, S. S.; Liu, C.; Cheng, H.-M. (Chem. Commun., 2012)

(untitled) - He, M. S.; Jiang, H.; Liu, B. L.; Fedotov, P. V.; Chernov, A. I.; Obraztsova, E. D.; Cavalca, F.; Wagner, J. B.; Hansen, T. W.; Anoshkin, I. V.; Obraztsova, E. A.; Belkin, A. V.; et al. (Sci. Rep., 2013)

(untitled) - Wang, H.; Wei, L.; Ren, F.; Wang, Q.; Pfefferle, L. D.; Haller, G. L.; Chen, Y. (ACS Nano, 2013)

(untitled) - Yang, F.; Wang, X.; Zhang, D. Q.; Yang, J.; Luo, D.; Xu, Z. W.; Wei, J. K.; Wang, J. Q.; Xu, Z.; Peng, F.; Li, X. M.; Li, R. M.; et al. (Nature, 2014)

(untitled) - Yang, F.; Wang, X.; Zhang, D. Q.; Qi, K.; Yang, J.; Xu, Z.; Li, M. H.; Zhao, X. L.; Bai, X. D.; Li, Y. (J. Am. Chem. Soc., 2015)

(untitled) - Zhang, S. C.; Tong, L. M.; Hu, Y.; Kang, L. X.; Zhang, J. (J. Am. Chem. Soc., 2015)

(untitled) - Reich, S.; Li, L.; Robertson, J. (Chem. Phys. Lett., 2006)

(untitled) - Ding, F.; Harutyunyan, A. R.; Yakobson, B. I. (Proc. Natl. Acad. Sci. U. S. A., 2009)

(untitled) - Rao, R.; Liptak, D.; Cherukuri, T.; Yakobson, B. I.; Maruyama, B. (Nat. Mater., 2012)

(untitled) - Liu, B. L.; Liu, J.; Tu, X. M.; Zhang, J. L.; Zheng, M.; Zhou, C. W. (Nano Lett., 2013)

(untitled) - Artyukhov, V. I.; Penev, E. S.; Yakobson, B. I. (Nat. Commun., 2014)

(untitled) - Wang, H.; Yuan, Y.; Wei, L.; Goh, K.; Yu, D. S.; Chen, Y. (Carbon, 2015)

(untitled) - Bandow, S.; Takizawa, M.; Hirahara, K.; Yudasaka, M.; Iijima, S. (Chem. Phys. Lett., 2001)

(untitled) - Bandow, S.; Hiraoka, T.; Yumura, T.; Hirahara, K.; Shinohara, H.; Iijima, S. (Chem. Phys. Lett., 2004)

(untitled) - Fujita, Y.; Niwa, N.; Bandow, S.; Iijima, S. (Appl. Phys. A, 2006)

(untitled) - Fujita, Y.; Bandow, S.; Iijima, S. (Chem. Lett., 2007)

(untitled) - Kramberger, C.; Waske, A.; Biedermann, K.; Pichler, T.; Gemming, T.; Büchner, B.; Kataura, H. (Chem. Phys. Lett., 2005)

(untitled) - Pfeiffer, R.; Kuzmany, H.; Kramberger, C.; Schaman, C.; Pichler, T.; Kataura, H.; Achiba, Y.; Kürti, J.; Zólyomi, V. (Phys. Rev. Lett., 2003)

(untitled) - Pfeiffer, R.; Simon, F.; Kuzmany, H.; Popov, V. N. (Phys. Rev. B, 2005)

(untitled) - Pfeiffer, R.; Holzweber, M.; Peterlik, H.; Kuzmany, H.; Liu, Z.; Suenaga, K.; Kataura, H. (Nano Lett., 2007)

(untitled) - Simon, F.; Kramberger, C.; Pfeiffer, R.; Kuzmany, H.; Zólyomi, V.; Kurti, J.; Singer, P. M.; Alloul, H. (Phys. Rev. Lett., 2005)

(untitled) - Simon, F.; Kukovecz, Á.; Kramberger, C.; Pfeiffer, R.; Hasi, F.; Kuzmany, H.; Kataura, H. (Phys. Rev. B, 2005)

(untitled) - Shiozawa, H.; Pichler, T.; Grüneis, A.; Pfeiffer, R.; Kuzmany, H.; Liu, Z.; Suenaga, K.; Kataura, H. (Adv. Mater., 2008)

(untitled) - Shiozawa, H.; Kramberger, C.; Pfeiffer, R.; Kuzmany, H.; Pichler, T.; Liu, Z.; Suenaga, K.; Kataura, H.; Silva, S. R. P. (Adv. Mater., 2010)

(untitled) - Kharlamova, M. V.; Sauer, M.; Saito, T.; Sato, Y.; Suenaga, K.; Pichler, T.; Shiozawa, H. (Nanoscale, 2015)

(untitled) - Shiozawa, H.; Pichler, T.; Kramberger, C.; Rümmeli, M.; Batchelor, D.; Liu, Z.; Suenaga, K.; Kataura, H.; Silva, S. R. P. (Phys. Rev. Lett., 2009)

(untitled) - Kataura, H.; Maniwa, Y.; Abe, M.; Fujiwara, A.; Kodama, T.; Kikuchi, K.; Imahori, H.; Misaki, Y.; Suzuki, S.; Achiba, Y. (Appl. Phys. A, 2002)

(untitled) - Kim, K. S.; Winograd, N. (Surf. Sci., 1974)

(untitled) - Löchel, B. P.; Strehblow, H. H. (J. Electrochem. Soc., 1984)

Chemistry of the elements - Greenwood, N. N.; Earnshaw, A. (Elsevier, 1997)

(untitled) - Leng, Y. G.; Shao, H. Y.; Wang, Y. T.; Suzuki, M.; Li, X. G. (J. Nanosci. Nanotechnol., 2006)

(untitled) - Sinharoy, S.; Levenson, L. L. (Thin Solid Films, 1978)

(untitled) - Kovács, G. J.; Bertóti, I.; Radnóczi, G. (Thin Solid Films, 2008)

(untitled) - Einarsson, E.; Murakami, Y.; Kadowaki, M.; Maruyama, S. (Carbon, 2008)

(untitled) - Picher, M.; Anglaret, E.; Arenal, R.; Jourdain, V. (Nano Lett., 2009)

(untitled) - Sharma, R.; Rez, P.; Brown, M.; Du, G. H.; Treacy, M. M. J. (Nanotechnology, 2007)

(untitled) - Marchand, M.; Journet, C.; Guillot, D.; Benoit, J.-M.; Yakobson, B. I.; Purcell, S. T. (Nano Lett., 2009)

(untitled) - Finnie, P.; Li-Pook-Than, A.; Lefebvre, J. (Nano Res., 2009)

(untitled) - Futaba, D. N.; Hata, K.; Yamada, T.; Mizuno, K.; Yumura, M.; Iijima, S. (Phys. Rev. Lett., 2005)

(untitled) - Puretzky, A. A.; Geohegan, D. B.; Jesse, S.; Ivanov, I. N.; Eres, G. (Appl. Phys. A, 2005)

(untitled) - Wirth, C. T.; Zhang, C.; Zhong, G. F.; Hofmann, S.; Robertson, J. (ACS Nano, 2009)

(untitled) - Meshot, E. R.; Plata, D. L.; Tawfick, S.; Zhang, Y. Y.; Verploegen, E. A.; Hart, A. J. (ACS Nano, 2009)

(untitled) - Louchev, O. A.; Laude, T.; Sato, Y.; Kanda, H. (J. Chem. Phys., 2003)

(untitled) - Zhu, L. B.; Xu, J. W.; Xiao, F.; Jiang, H. J.; Hess, D. W.; Wong, C. P. (Carbon, 2007)

(untitled) - Wood, R. F.; Pannala, S.; Wells, J. C.; Puretzky, A. A.; Geohegan, D. B. (Phys. Rev. B, 2007)

(untitled) - Vinten, P.; Lefebvre, J.; Finnie, P. (Chem. Phys. Lett., 2009)

(untitled) - Yasuda, S.; Futaba, D. N.; Yamada, T.; Yumura, M.; Hata, K. (Nano Lett., 2011)

(untitled) - Chen, G. H.; Davis, R. C.; Kimura, H.; Sakurai, S.; Yumura, M.; Futaba, D. N.; Hata, K. (Nanoscale, 2015)

(untitled) - Zhang, C.; Pisana, S.; Wirth, C. T.; Parvez, A.; Ducati, C.; Hofmann, S.; Robertson, J. (Diamond Relat. Mater., 2008)

(untitled) - Li-Pook-Than, A.; Lefebvre, J.; Finnie, P. (J. Phys. Chem. C, 2010)

(untitled) - Rao, R.; Pierce, N.; Liptak, D.; Hooper, D.; Sargent, G.; Semiatin, S. L.; Curtarolo, S.; Harutyunyan, A. R.; Maruyama, B. (ACS Nano, 2013)

(untitled) - Zhu, L. B.; Hess, D. W.; Wong, C.-P. (J. Phys. Chem. B, 2006)

(untitled) - Meshot, E. R.; Hart, A. J. (Appl. Phys. Lett., 2008)

(untitled) - Pal, S. K.; Talapatra, S.; Kar, S.; Ci, L.; Vajtai, R.; Borca-Tasciuc, T.; Schadler, L. S.; Ajayan, P. M. (Nanotechnology, 2008)

(untitled) - In, J. B.; Grigoropoulos, C. P.; Chernov, A. A.; Noy, A. (ACS Nano, 2011)

(untitled) - Pirard, S. L.; Douven, S.; Bossuot, C.; Heyen, G.; Pirard, J.-P. (Carbon, 2007)

(untitled) - van de Burgt, Y.; Bellouard, Y.; Mandamparambil, R. (Phys. Chem. Chem. Phys., 2014)

(untitled) - Liu, K.; Jiang, K. L.; Feng, C.; Chen, Z.; Fan, S. S. (Carbon, 2005)

(untitled) - Hsieh, C.-T.; Lin, Y.-T.; Lin, J.-Y.; Wei, J.-L. (Mater. Chem. Phys., 2009)

(untitled) - Ni, L.; Kuroda, K.; Zhou, L.-P.; Kizuka, T.; Ohta, K.; Matsuishi, K.; Nakamura, J. (Carbon, 2006)

(untitled) - Baker, R. T. K. (Carbon, 1989)

(untitled) - Choi, Y. C.; Shin, Y. M.; Lee, Y. H.; Lee, B. S.; Park, G.-S.; Choi, W. B.; Lee, N. S.; Kim, J. M. (Appl. Phys. Lett., 2000)

(untitled) - Chiang, W.-H.; Sankaran, R. M. (Diamond Relat. Mater., 2009)

(untitled) - Patole, S. P.; Kim, H.; Choi, J.; Kim, Y.; Baik, S.; Yoo, J. B. (Appl. Phys. Lett., 2010)

(untitled) - Cervantes-Sodi, F.; McNicholas, T. P.; Simmons, J. G., Jr; Liu, J.; Csányi, G.; Ferrari, A. C.; Curtarolo, S. (ACS Nano, 2010)

(untitled) - Huang, Z. P.; Wang, D. Z.; Wen, J. G.; Sennett, M.; Gibson, H.; Ren, Z. F. (Appl. Phys. A, 2002)

(untitled) - Kim, N. S.; Lee, Y. T.; Park, J.; Han, J. B.; Choi, Y. S.; Choi, S. Y.; Choo, J.; Lee, G. H. (J. Phys. Chem. B, 2003)

(untitled) - Kim, N. S.; Lee, Y. T.; Park, J. H.; Ryu, H.; Lee, H. J.; Choi, S. Y.; Choo, J. B. (J. Phys. Chem. B, 2002)

(untitled) - Gorbunov, A.; Jost, O.; Pompe, W.; Graff, A. (Carbon, 2002)

(untitled) - Hofmann, S.; Ducati, C.; Robertson, J.; Kleinsorge, B. (Appl. Phys. Lett., 2003)

(untitled) - Lee, Y. T.; Kim, N. S.; Park, J.; Han, J. B.; Choi, Y. S.; Ryu, H.; Lee, H. J. (Chem. Phys. Lett., 2003)

(untitled) - Bartsch, K.; Biedermann, K.; Gemming, T.; Leonhardt, A. (J. Appl. Phys., 2005)

(untitled) - Kim, K.-E.; Kim, K.-J.; Jung, W. S.; Bae, S. Y.; Park, J.; Choi, J.; Choo, J. (Chem. Phys. Lett., 2005)

(untitled) - Kim, S. H.; Zachariah, M. R. (J. Phys. Chem. B, 2006)

(untitled) - Bronikowski, M. J. (J. Phys. Chem. C, 2007)

(untitled) - Chiang, W.-H.; Sankaran, R. M. (Appl. Phys. Lett., 2007)

(untitled) - Nessim, G. D.; Seita, M.; O'Brien, K. P.; Hart, A. J.; Bonaparte, R. K.; Mitchell, R. R.; Thompson, C. V. (Nano Lett., 2009)

(untitled) - Hsieh, C.-T.; Lin, Y.-T.; Chen, W.-Y.; Wei, J.-L. (Powder Technol., 2009)

(untitled) - Voelskow, K.; Becker, M. J.; Xia, W.; Muhler, M.; Turek, T. (Chem. Eng. J., 2014)

(untitled) - Lee, Y. T.; Park, J.; Choi, Y. S.; Ryu, H.; Lee, H. J. (J. Phys. Chem. B, 2002)

(untitled) - Lee, Y. T.; Kim, N. S.; Bae, S. Y.; Park, J.; Yu, S.-C.; Ryu, H.; Lee, H. J. (J. Phys. Chem. B, 2003)

(untitled) - Chen, M.; Chen, C.-M.; Shi, S.-C.; Chen, C.-F. (Jpn. J. Appl. Phys., 2003)

(untitled) - Chhowalla, M.; Teo, K. B. K.; Ducati, C.; Rupesinghe, N. L.; Amaratunga, G. A. J.; Ferrari, A. C.; Roy, D.; Robertson, J.; Milne, W. I. (J. Appl. Phys., 2001)

(untitled) - Ducati, C.; Alexandrou, I.; Chhowalla, M.; Amaratunga, G. A. J.; Robertson, J. (J. Appl. Phys., 2002)

(untitled) - Ma, H.; Pan, L. J.; Nakayama, Y. (Carbon, 2011)

Introduction to surface chemistry and catalysis - Somorjai, G. A. (Wiley, 1994)

(untitled) - Haruta, M.; Yamada, N.; Kobayashi, T.; Iijima, S. (J. Catal., 1989)

(untitled) - Tsunoyama, H.; Sakurai, H.; Tsukuda, T. (Chem. Phys. Lett., 2006)

(untitled) - Henry, C. R. (Surf. Sci. Rep., 1998)

(untitled) - Kataura, H.; Kumazawa, Y.; Maniwa, Y.; Ohtsuka, Y.; Sen, R.; Suzuki, S.; Achiba, Y. (Carbon, 2000)

(untitled) - Page, A. J.; Minami, S.; Ohta, Y.; Irle, S.; Morokuma, K. (Carbon, 2010)

(untitled) - Baker, R. T. K.; Chludzinski, J. J., Jr; Dudash, N. S.; Simoens, A. J. (Carbon, 1983)

(untitled) - Baker, R. T. K.; Chludzinski, J. J., Jr; Lund, C. R. F. (Carbon, 1987)

Concepts of Modern Catalysis and Kinetics - Chorkendorff, I.; Niemantsverdriet, J. W. (Wiley-VCH, 2007)

(untitled) - Diamond, S.; Wert, C. (Trans. Metall. Soc. AIME, 1967)

(untitled) - Morgan, D. W.; Kitchener, J. A. (Trans. Faraday Soc., 1954)

(untitled) - Grace, R. E.; Derge, G. (Trans. Am. Inst. Min., Metall. Pet. Eng., 1958)

(untitled) - Kovenskiy, I. I. (Phys. Met. Metallogr., 1963)

(untitled) - Schmidt, F. A.; Warner, J. C. (J. Less-Common Met., 1972)

(untitled) - Rudman, P. S. (Trans. Metall. Soc. AIME, 1967)

(untitled) - Wells, C.; Batz, W.; Mehl, R. F. (Trans. Am. Inst. Min., Metall. Pet. Eng., 1950)

(untitled) - Smith, R. P. (Trans. Metall. Soc. AIME, 1964)

(untitled) - Mojica, J. F.; Levenson, L. L. (Surf. Sci., 1976)

Smithells' Metals Reference Book - Brandes, E. A.; Brook, G. B. (Butterworth-Heinemann Ltd, 1992)

(untitled) - Silcocks, C. G. (Proc. R. Soc. London, Ser. A, 1957)

(untitled) - Palmer, H. B.; Dormish, F. L. (J. Phys. Chem., 1964)

(untitled) - Zhang, Y.; Smith, K. J. (Catal. Today, 2002)

(untitled) - Li, J.; Kazakov, A.; Dryer, F. L. (J. Phys. Chem. A, 2004)

(untitled) - Zhong, G. F.; Iwasaki, T.; Robertson, J.; Kawarada, H. (J. Phys. Chem. B, 2007)

(untitled) - Amama, P. B.; Pint, C. L.; McJilton, L.; Kim, S. M.; Stach, E. A.; Murray, P. T.; Hauge, R. H.; Maruyama, B. (Nano Lett., 2009)

(untitled) - Ding, F.; Xu, Z. W.; Yakobson, B. I.; Young, R. J.; Kinloch, I. A.; Cui, S. A.; Deng, L. B.; Puech, P.; Monthioux, M. (Phys. Rev. B, 2010)

(untitled) - Liu, X. J.; Kuzmany, H.; Saito, T.; Pichler, T. (Phys. Status Solidi B, 2011)

(untitled) - Briones, A.; Liu, X. J.; Kramberger, C.; Saito, T.; Pichler, T. (Phys. Status Solidi B, 2011)

(untitled) - Kharlamova, M. V.; Sauer, M.; Saito, T.; Krause, S.; Liu, X.; Yanagi, K.; Pichler, T.; Shiozawa, H. (Phys. Status Solidi B, 2013)

(untitled) - Kharlamova, M. V.; Sauer, M.; Egorov, A.; Kramberger, C.; Saito, T.; Pichler, T.; Shiozawa, H. (Phys. Status Solidi B, 2015)